2014
DOI: 10.1039/c3ob41746h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of biscarbazoles by palladium-catalyzed twofold C–N coupling and C–H activation reactions

Abstract: A new and efficient strategy for the synthesis of 3,9'- and 2,9'-biscarbazoles was developed. Our strategy relies on the cyclization of 1,1'-biphenyl-2,2'-diyl bis(trifluoromethanesulfonate) with 4- or 3-anisidine, transformation of the methoxy to a triflate group and subsequent oxidative Pd-catalyzed cyclization with various anilines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…More recently, Dang, Langer, and their co-workers reported a multistep route to biscarbazoles 148a and 148b ( Scheme 29 , next page) involving three Pd-catalyzed coupling reactions of anilines. 134 First, inter- and intramolecular N-arylation of p -anisidines (top) or m -anisidines (bottom) with bistriflate 146 furnished carbazoles 147a and 147b . Subsequent conversion of the methoxy groups into triflates, followed by an N-arylation/C–H activation sequence, successfully introduced a second carbazole into the structure, yielding 3,9′- and 2,9′-biscarbazoles ( 148a and 148b ).…”
Section: Anilinesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Dang, Langer, and their co-workers reported a multistep route to biscarbazoles 148a and 148b ( Scheme 29 , next page) involving three Pd-catalyzed coupling reactions of anilines. 134 First, inter- and intramolecular N-arylation of p -anisidines (top) or m -anisidines (bottom) with bistriflate 146 furnished carbazoles 147a and 147b . Subsequent conversion of the methoxy groups into triflates, followed by an N-arylation/C–H activation sequence, successfully introduced a second carbazole into the structure, yielding 3,9′- and 2,9′-biscarbazoles ( 148a and 148b ).…”
Section: Anilinesmentioning
confidence: 99%
“… In the presence of L26 , a variety of primary anilines and several alkylamines were successfully coupled with 2,2′-dihalobiphenyls to provide the desired N-substituted carbazoles ( 145 ) in 34–99% yield. More recently, Dang, Langer, and their co-workers reported a multistep route to biscarbazoles 148a and 148b (Scheme , next page) involving three Pd-catalyzed coupling reactions of anilines . First, inter- and intramolecular N-arylation of p -anisidines (top) or m -anisidines (bottom) with bistriflate 146 furnished carbazoles 147a and 147b .…”
Section: Anilinesmentioning
confidence: 99%
“…Regarding the catalytic use of metallic nanoparticles, in particular those of palladium and copper, as a current strategy in organic synthesis in virtue of their wide scope of chemical reactions compared to homogeneous catalytic systems, in this review, the state of the art on the preparation of fine chemicals from multi-step transformations from a sustainable point of view is analyzed [ 7 , 8 , 9 , 10 , 11 , 12 ]. During the last decade, a prominent review was reported by Buchwald et al (2016) regarding homogeneous palladium-catalyzed multi-step transformations, mainly in C–N cross-coupling reactions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bicarbazole (BCz) derivatives could further increase the structural diversity of the Cz framework through multifarious ways of linking two Cz units. Chemically speaking, BCz derivatives include 15 isomers (Figure ), namely, 1,1′‐, 1,2′‐,, 1,3′‐,, 1,4′‐,, 2,2′‐, 2,3′‐, 2,4′‐, 3,3′‐, 3,4′‐, 4,4′‐,, 1,9′‐, 2,9′‐, 3,9′‐, 4,9′‐, and 9,9′‐BCz . Although many BCz derivatives have been prepared and used as OLED materials, a large number of new materials based on BCz demonstrate great potential for OLED applications.…”
Section: Introductionmentioning
confidence: 99%